Development of IoT Control System Prototype for Flood Prevention in Bandung Area - Permatasari, Yessy; Firdaus, M Ridwan; Zuhdi, Hafidh; Fakhrurroja, Hanif; Musnansyah, Ahmad (JOIV : International Journal on Informatics Visualization, 2023)
Bandung is one of the areas with high rainfall that can increase the volume of river water, which, if not handled properly, has the potential for significant floods that can cause material damage and loss of life. With this problem, the authors' rationale for designing a control system for flood prevention. This system develops prototypes using Internet of Things technology and fuzzy logic. For Internet of Things technology, the author uses Arduino, which controls sensors and actuators, while Raspberry Pi is used to process data. In addition, the author uses ultrasonic sensors to measure the water level and a water pump to control the water level. So, if the water level exceeds the specified limit, the pump will move the water to another place, in this prototype, using an aquarium. For fuzzy logic, the criteria used are dry, filled, and full. In addition, this system is equipped with a website-based dashboard used to monitor real-time data from the sensor. The results of this study indicate the system is running well, with an average error of 32.2%. This indicates that the system has been well designed because the errors obtained are feasible to be minor, although there are several influencing factors, such as prototype construction and sensor readings. Thus, this prototype can be applied as a reference for making a real system for flood control.